The relationships between agency, communion and the selected religiosity measures in Polish Catholics - Tychmanowicz, Anna; Goździewicz-Rostankowska, Agata; Zarzycka, Beata (Studia Psychologica: Theoria et praxis, 2017)
Agency and communion are two important aspects of human existence. On the one hand, an individual is the executor of their goals (agency); on the other hand, every human is also a member of the community and a participant in social relations (communion; Bakan, 1966; Gebauer, Paulhus, Neberich, 2013; Wojciszke, 2010). The literature emphasizes the relationships of agency and communion with many aspects of personality, well-being, social functioning and their role in the shaping of religious beliefs and value systems. The goal of this study is to analyse the relationship between agency and communion and multidimensional religiosity among Polish Catholics. Among the problems analysed there were: the relationships of agentic and communal orientation with the dimensions of religiosity (Interest, Beliefs, Prayer, Religious Experience, Cult) and post-critical beliefs (Orthodoxy, Relativism, External Critique, Second Naiveté). A total of 308 individuals were studied (23% men) aged from 18 to 27 (M = 20.84, SD = 1.60) However, for the analyses data from 249 participants (Catholics) were collected. The study used the Centrality of Religiosity Scale by Huber, Post-Critical Belief Scale by Hutsebaut and the Scale of Agency and Communion by Wojciszke (Self-description Questionnaire 30). Above all, the results obtained indicate a positive relationship between the community orientation and traditional religiosity. The results of cluster analysis also suggest that there are relationships between agency and religiosity.